Answer:
y = -4x - 11.
Step-by-step explanation:
Its slope = slope of y = -4x + 2, which is -4.
Using point-slope form of a straight line
y - y1 = m(x - x1)
y - (-3) = -4(x - (-2))
y + 3 = -4(x + 2)
y = -4x - 8 - 3
y = -4x - 11.
Answer:
That is so easyyyyyyyyy
Step-by-step explanation:
The answer for b is 18 ; 2×6 +3×2
then for c. 24; 2×6×2
Answer:
-3
Step-by-step explanation:
3(-2)/2
-6/2 = -3
Answer:
asymptotically stable.
Step-by-step explanation:
Equilibrium solutions in which solutions that starts near and then moves away from equilibrium solutions are asymptotically unstable. Equilibrium solutions which solutions starts nears and then move towards the equilibrium are asymptotically stable.